The Brontës and masculinity - Nyborg, E (2016)
This is the first comprehensive study of the Brontës' representations of masculinity. In it, I analyse the ways this family of writers depicted forms of masculinity as they developed from late-Romantic child writers to mature novelists and poets of the Victorian period. My chief concern is to situate the Brontës within the historical period of 1829-1855, from Charlotte's first Glass Town stories to the time of her death. This thesis examines the Brontë siblings' complete body of work, including Branwell's contributions to the Angrian saga, Emily's and Anne's Gondal poetry, and Charlotte's and Emily's Belgian devoirs. In undertaking this work, I model my approach on Heather Glen's precise, historical readings in Charlotte Brontë: The Imagination in History (2002), as well as John Tosh's social historical examination of Victorian masculinity, particularly in A Man’s Place: Masculinity and the Middle-Class Home (1999). This study examines representations of masculinity in the modes of cultural production the Brontës were exposed to: contemporary periodicals, poetry, fiction, domestic handbooks, gift books, educational texts, clerical and medical handbooks, and labour management treatises. I track the Brontës' various engagements with and revisions of Byronic and Carlylean forms of masculinity, as well as the rise and fall of the silver fork dandy and the emergence of both the Victorian self-made man and the new professional. This study considers how the Brontës' representations of gender formation were affected by different modes of familial literary production and collaboration. Though the Brontës shared their creative works from a young age and grew up within the same domestic literary culture, the siblings' depictions of masculinity diverge, and each sister situates herself within various cultural contexts relating, for example, to child-rearing, romance, and professional conduct. My thesis is organised thematically, with chapters examining heroic, domestic, and professional representations of masculinity in the Brontës' works.